Control de thrips con la técnica de bioensayo en Pasaje - Jaramillo Vega, Ronald Adolfo (2012)
The research was conducted in the parish Caña Quemada, Passage of the canton, province of El Oro, in the Hcda. Celia Maria S.A. with the aim of finding new natural compounds more effective for controlling adult thrips which together with other pests cluster losses occur above 15 %. The objectives were: 1. To quantify the toxicity of diatom powder suspensions alone and mixed with organic insecticides against thrips tubuliferos and red spot bioassays. 2. Testing the effectiveness of the insecticide over other traditional insecticides with organic certification. The treatments studied were: T1 tierra de diatomeas 5 ml, T2 mullein extract 10 ml, T3 neem oil 5 ml, 6 ml bromorex T4, T5 control 0 ml. For laboratory testing was used completely randomized design with five treatments and five repetitions, totaling 25 experimental units. The variables analyzed were: number of live and dead insects per experimental unit, adult mortality and mortality corrected by Abbott's formula. Statistical analysis revealed that insecticide treatments gave a high mortality rate with 7,4 T1 and T5 was the lowest, most individuals survive with 8,6 occurred in the control. In T1 tierra de diatomeas 5 ml, mortality of adults varied ithin the range of 4,0 to 6.4 with an average of 5,2 %. The corrected mortality bromorex obtained the highest level with 90,47 % and 87,54 % to 87,65 with two levels with mullein and neem oil with the lowest level was the 5 control 0 ml treatment.